IMPLEMENTASI PENANAMAN LIFE SKILL PADA USIA DINI DI TPA ALBA MANDIRI PACITAN - Khusnul Hamdani, Mohammad (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
What is happening in the field now is that a person's life skills have become a job for parents to train their independence. The teenage years of today's children lead to a life of extravagance and are oriented towards a fantasy world. Another orientation of teenagers aimed at cyberspace cannot be separated from gadgets and the internet. Bad influences nowadays make it a challenge for parents to direct their children to the skills they have. Life skills are an offer to minimize problems that are only oriented to the virtual world. From an early age, children need to be introduced to developing life skills such as adapting to creativity, innovation and conceptualizing skills. Training at Alba Mandiri TPA by utilizing various sources with constructive activities. TPA Alba Mandiri provides training to its students to provide provisions from an early age to have future skills with various problems and life cycles.